Two new dragonfly species (Odonata: Anisoptera: Aeshnidae) from north-eastern India - Joshi, Shantanu; Kunte, Krushnamegh (Zootaxa, 2017)
Cephalaeschna acanthifrons sp. nov. collected from Eaglenest Wildlife Sanctuary, West Kameng District, Arunachal Pradesh, India, and Planaeschna poumai sp. nov. collected from two localities in Senapati District, Manipur, India, are described and compared with congeneric species. These records also represent the first reports of these obscure genera from India in the past 30 years.